Pengembangan LKPD Menggunakan Book Creator Berbasis RADEC di Kelas III SD - Ragil Stevani Ragil Stevani (Jurnal Elementaria Edukasia, 2023)
The lack of use of technology in developing LKPD makes the appearance of LKPD less attractive for students to work on. Therefore, it is necessary to use appropriate technology and learning models as well as interesting worksheets to increase students' interest in learning. One of them is by using Book Creator. This type of research is development research using the Research and Development (R&D) method using the ADDIE model. The material validity test in the development of this LKPD obtained results of 93.75%, in the very valid category, the linguistic validity test results were 91.6% in the very valid category, and the media validity test results were 96.87% in the very valid category. The percentage of 91.6% for the teacher's response questionnaire and 92.8% was obtained from the results of the practicality test for the student's response questionnaire in the pilot school. The percentage of 95.83% for the teacher response questionnaire and 93% was obtained from the practicality test results for the student response questionnaire in research schools.